Knowledge and attitude towards lesbian, gay, bisexual, and transgender healthcare concerns: A cross-sectional survey among undergraduate nursing students in a Philippine state university - Ryan Michael F. Oducado (Belitung Raya Foundation, Indonesia, 2023)
Background: Recently, there has been an increasing concern regarding matters concerning the LGBT community that should not be overlooked. Even though the Philippines is among the Asian nations with strong public tolerance towards homosexuals, numerous individuals still encounter discrimination. And while studies have been conducted elsewhere, the literature is limited among Filipino nursing students. Objective: This research assessed the knowledge and attitude towards lesbian, gay, bisexual, and transgender (LGBT) healthcare concerns among nursing students in the Philippines. Methods: A descriptive, cross-sectional survey was conducted among nursing students (N = 354) in a public university in the Philippines. The Nursing Students’ Knowledge and Attitudes of LGBT Health Concerns was used to gather survey data online in April 2022, and data were analyzed using IBM SPSS version 26 software. Results: While a large majority of nursing students had positive attitudes, many had only low to moderate knowledge about LGBT healthcare concerns, although no significant correlation (p = 0.081) was found between knowledge and attitude. There were significant differences in knowledge based on gender (p = 0.049), religious affiliation (p = 0.023), and academic year level (p <0.001). A significant difference was also identified in attitude based on sexual orientation (p <0.001). Conclusion: Certain measures should be taken to address the gaps in the curricular content of undergraduate nursing programs directed at the LGBT topic to deliver culturally competent care grounded in evidence-based practices for LGBT individuals.